2014
DOI: 10.1016/s1470-2045(13)70333-4
|View full text |Cite
|
Sign up to set email alerts
|

The scope of nanoparticle therapies for future metastatic melanoma treatment

Abstract: Metastatic melanoma is a highly aggressive malignancy that has traditionally been very difficult to treat. However, after decades of basic research into the signal transduction pathways that promote cancer cell survival, chemoresistance, growth, and crosstalk with the immune system, targeted therapies have now been developed that offer improved survival for patients with metastatic melanoma. Some of the most promising therapies that have been developed include ipilimumab, an anti-cytotoxic T lymphocyte antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 73 publications
0
56
0
Order By: Relevance
“…We initially studied the biodistribution of NDHCs in mice organs, and found that a substantial amount of NDHC was accumulated in tumor, as well as other organs including liver, spleen and kidneys (Supplementary Figure 10). As the size of NDHCs was around 100 nm, it probably accumulated in the tumor through a well-studied enhanced permeation and retention effect [21,22]. The antitumor efficacy of PTX-loaded NDHC delivery was then performed by future science group Nanoparticle-dendrimer hybrid nanocapsules for therapeutic delivery Research Article intravenous injection of PTX-loaded NDHCs, into C57BL6 mice bearing melanoma tumors.…”
Section: Resultsmentioning
confidence: 99%
“…We initially studied the biodistribution of NDHCs in mice organs, and found that a substantial amount of NDHC was accumulated in tumor, as well as other organs including liver, spleen and kidneys (Supplementary Figure 10). As the size of NDHCs was around 100 nm, it probably accumulated in the tumor through a well-studied enhanced permeation and retention effect [21,22]. The antitumor efficacy of PTX-loaded NDHC delivery was then performed by future science group Nanoparticle-dendrimer hybrid nanocapsules for therapeutic delivery Research Article intravenous injection of PTX-loaded NDHCs, into C57BL6 mice bearing melanoma tumors.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, metastatic melanoma is arguably one of the hardest cancers to treat and has very few treatment options in the clinic. As an immunogenic cancer, it is known the immune system plays a role in progression of the disease [70]. Therefore, the immune system was targeted as a potential solution to molecular inhibitor resistance in metastatic melanoma and other cancers.…”
Section: Immune Checkpoint Modulatorsmentioning
confidence: 99%
“…Morbidity and mortality indices are highly variable worldwide-being rare in nations of Asian and African origin and almost considered epidemic in countries of Caucasian predominance (2,3). When diagnosed early, as a localized cutaneous tumor, melanoma can be surgically removed with a good prognosis (4).…”
Section: Introductionmentioning
confidence: 99%
“…Temozolomide, a DTIC derivative, has the ability to cross the blood-brain barrier and is a first-line therapy for brain metastases (9). Recently, BRAF inhibitors (Vemurafenib, Dabrafenib) and MEK inhibitor (Trametinib) have been approved by the FDA for treating BRAF-mutated melanoma which is nearly found in 50% of cases (2). Immunotherapy is another promising treatment option in metastatic melanoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation